The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00405-016-4171-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of laryngoceles by transoral robotic surgery

Abstract: We herein report our experience with the management of laryngoceles using transoral robotic surgery (TORS). A bicentric retrospective study was conducted from November 2009 to September 2015. The inclusion criteria were treatment of a laryngocele by TORS and no malignancy on definitive histopathology. Surgery was performed using the Da Vinci (Intuitive) surgical robot. Surgical methods and post-operative outcomes were evaluated. Eight patients (four men and four women) presenting with a laryngocele (one bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…32 Some studies also report cases of resection by TORS of retropharyngeal schwannoma, 33 hypopharyngeal lipoma 34 or ectopic base-oftongue thyroid glands. [42][43][44] F IGUR E 5 Patient B, "en bloc" resection of a 7-cm lipoma [Color figure can be viewed at wileyonlinelibrary.com] CHABRILLAC ET AL | 5 Very few laryngeal tumors removed by TORS have been reported (ie, schwannoma, lipoma, or hemangioma).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Some studies also report cases of resection by TORS of retropharyngeal schwannoma, 33 hypopharyngeal lipoma 34 or ectopic base-oftongue thyroid glands. [42][43][44] F IGUR E 5 Patient B, "en bloc" resection of a 7-cm lipoma [Color figure can be viewed at wileyonlinelibrary.com] CHABRILLAC ET AL | 5 Very few laryngeal tumors removed by TORS have been reported (ie, schwannoma, lipoma, or hemangioma).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] In addition, interest in TORS for the resection of laryngocele is already reported. [42][43][44] F IGUR E 5 Patient B, "en bloc" resection of a 7-cm lipoma [Color figure can be viewed at wileyonlinelibrary.com] CHABRILLAC ET AL | 5 6 | C ONCL US I ON Although the literature on this subject is sparse, this surgical technique had few complications and resulted in short hospital stays, with satisfactory functional and recurrence outcomes. Thus, it seems legitimate to pursue the development of this procedure, and to broaden its indications in head and neck surgery.…”
Section: Ter Atu Re Rev I Ewmentioning
confidence: 99%
“…Lisan et al 14 reported on the use of a laserassisted TORS approach for a combined laryngomucocele , in which both the internal and external components of the were managed successfully via a minimally invasive approach, with no evidence of recurrence. 14,15 Most reported cases (45%) resected by TORS were combined laryngoceles, [14][15][16][17][18][19] with no reported recurrences in any cases of combined laryngocele managed by TORS, up to 3 years after treatment. Only three patients required a covering tracheostomy, and they were successfully decannulated an average of 2 days postprocedure.…”
Section: Emergencymentioning
confidence: 94%
“…Although TORS has been primarily used in excision of laryngeal malignancies, the same methods have been used in excision of laryngoceles as well. The first study using TORS for the excision of laryngoceles was first published in 2013, and since then several other case series have been published as well . The purpose of this study was to extend the TORS technique in excision of a laryngocele with preservation of the laryngeal structures and showcase the surgical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…The first study using TORS for the excision of laryngoceles was first published in 2013, and since then several other case series have been published as well. [11][12][13][14][15][16] The purpose of this study was to extend the TORS technique in excision of a laryngocele with preservation of the laryngeal structures and showcase the surgical considerations.…”
Section: Introductionmentioning
confidence: 99%